Development and Validation of Learning Strategy for Creative Thinking Skills Empowerment: STEM-Based E-Modules - Lina Listiana; Fathinatul Millah; Peni Suharti (Postgraduate, University of Mataram, 2023)
The feasibility on the learning tools is crucial because it ensures the validity of the data and information obtained. This study aims to describe the validity and reliability of STEM-based learning e-modules to train creative thinking skills, describe the effectiveness of STEM- based learning e-modules creative thinking skills, and describe student responses after learning using STEM-based e-modules. This research is Research and Development (R&D). The development modul used is the 4-D device development model. There are consist of the define, design, develop, and disseminate stage. The data were analysed descriptively quantitatively. The target of the e-modules trial was 11 student of class X IPA SMAM 4 Sidayu, Gresik, Indonesia. The data collecting techniques using validation techniques, tests, and questionnaires. The results were the validity of STEM-based e-modules to train creative thinking skills obtained 73.25% which is included in the valid category and can be tested on students. The data were analysed descriptively throught T-test and N-Gain. From the research results, it was concluded that the e-modules media is declared valid, STEM based e-modules are effective enough to train creative thinking skills, and student responses to e-modules are very good